ТЕХНИКА ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИ ТАЛАБАЛАРИДА КАСБИЙ КОМПЕТЕНЦИЯЛАРНИ РИВОЖЛАНТИРИШ ИМКОНИЯТЛАРИ - Адизова, С.Ю. (SCIENCE and SOCIETY, 2022)
The article is devoted to the analysis of shortcomings and problems, opportunities for the formation of professional competencies and technical abilities among students of engineering and technical specialties. The quality of training of engineers and technicians in the system of technical higher education depends, first of all, on the formed professional competencies and the intellectual development of future specialists.
Keywords: competence; chartered Engineer; engineering ability; cognitive; motivation